New construction of Z‐complementary pairs. Issue 8 (1st April 2016) - Li, Xudong; Mow, Wai Ho; Niu, Xianhua
Abstract : A Z‐complementary pair may be used as an alternative of a Golay complementary pair in many engineering applications. A new simple approach to generate more equal length Z‐complementary pairs is proposed. It is proved that a new Z‐complementary pair is composed of a linear combination of a complex Z‐complementary pair and the same linear combination of its mate. In particular, constructions of ternary and quadriphase Z‐complementary pairs based on binary Z‐complementary pairs and their mates are proposed.